RELATIONSHIP BETWEEN LEVEL KNOWLEDGE AND SUPERVISION TO THE BEHAVIOR OF APD APPLICATION IN CONSTRUCTION WORKERS PT WIKA BETON BOYOLALI - Fauzi Jatmiko; Haris Setiyawan; Tutug Bolet Atmojo (Universitas Darussalam Gontor, 2017)
The construction sector is one of the highest accidents. Most accidents are caused by unsafe acts, one of which is the failure to use PPE. The behavior of PPE is influenced by many factors including knowledge and supervision. This study aims to determine the relationship between the level of knowledge and supervision of the use of PPE in construction workers PT WIKA Beton Boyolali. This research is an observational analytic research with Cross Sectional approach with sampling technique that is Simple Random Sampling. The sample of the study was 54 male laborers. Level of Knowledge, Control and Behavior of Use of PPE is measured using a questionnaire. The data obtained were analyzed by Gamma and Somers'd test for independent variable relationship with dependent variable, then for multivariate analysis with Multiple Logistic Regression test. The result shows that there is correlation between knowledge level with behavioral usage of APD at significance value p = 0.018 and value r = 0.538 and relationship between supervision with behavior of APD usage at significance value p = 0.012 and value r = 0.291. Based on the multivariate analysis, it was found that the knowledge level was the most influential variable on the behavior of APD with p-value = 0.005 and OR = 37.263, then control with p-value = 0.038 and OR = 9.048 and the working period with p-value = 0.074 and OR = 0.115. Conclusion There is a significant relationship between the level of knowledge and supervision of the behavior of PPE. The variable that has the most influence on the behavior of PPE is the level of knowledge.Keywords: Knowledge, Supervision, Behavior, APD, Construction Worker